2013
DOI: 10.2337/db12-0584
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Deficiency of Nrf2 in ob/ob Mice Results in Severe Metabolic Syndrome

Abstract: Nuclear factor E2–related factor 2 (Nrf2) is a transcription factor that functions as a master regulator of the cellular adaptive response to oxidative stress. Our previous studies showed that Nrf2 plays a critical role in adipogenesis by regulating expression of CCAAT/enhancer-binding protein β and peroxisome proliferator–activated receptor γ. To determine the role of Nrf2 in the development of obesity and associated metabolic disorders, the incidence of metabolic syndrome was assessed in whole-body or adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 45 publications
9
116
1
2
Order By: Relevance
“…Previous studies demonstrated that Nrf2 inhibited onset and progression of NAFLD caused by HFD by activation of cellular antioxidant defense system (Okada et al 2013). Moreover, Nrf2 showed great ability in the regulation of lipogenesis, lipolysis (Xue et al 2013), and fibrosis (Shimozono et al Fig. 4 Effect of MLE on plasma and hepatic oxidative stress-related markers in high-fat diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies demonstrated that Nrf2 inhibited onset and progression of NAFLD caused by HFD by activation of cellular antioxidant defense system (Okada et al 2013). Moreover, Nrf2 showed great ability in the regulation of lipogenesis, lipolysis (Xue et al 2013), and fibrosis (Shimozono et al Fig. 4 Effect of MLE on plasma and hepatic oxidative stress-related markers in high-fat diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies demonstrated that Nrf2 inhibited onset and progression of NAFLD caused by HFD through activation of antioxidant defense system (Okada et al 2013). Nrf2 showed the ability to regulate lipogenesis, lipolysis (Xue et al 2013), and fibrosis (Shimozono et al 2013) in NAFLD. In addition, Nrf2 can decrease the levels of oxidative stress by induction of defensive antioxidant enzymes such as HO-1 (Su et al 2013) and modulate lipid metabolism and fibrosis in liver.…”
Section: Introductionmentioning
confidence: 95%
“…Additional studies utilizing the ob/ob genetic model of obesity have yielded varied results. Nrf2 knock-out animals crossed into the ob/ob mouse background, using either a whole animal or fatspecific Nrf2 knock-out, demonstrated that loss of Nrf2 resulted in decreased adipose tissue mass yet aggravated insulin resistance, hyperglycemia, and hypertriglyceridemia (81). This seems to demonstrate that in genetic models of obesity and diabetes, the results of Nrf2 modulation can vary drastically, depending on the specific conditions of the model.…”
Section: ) Was Not Altered In Nrf2mentioning
confidence: 93%
“…Targeted deletion of Nrf2 in mice causes developmental defects in adipogenesis and hematopoiesis, in addition to many oxidative stress defects upon treatment with xenobiotic agents. [19][20][21][22][23] Nrf2 can directly bind and activate adipogenic genes such as peroxisome proliferator-activated receptor γ (Pparγ) 21 and retinoid X receptor α (RXRA). 24 Nrf2 controls hematopoietic stem cell functions through transcriptional regulation of CXCR4.…”
Section: Regulation Of Developmentalmentioning
confidence: 99%